Risk of early recurrence and mortality in high-risk myocardial infarction patients: A population-based linked data study - Lee Nedkoff; Tom Briffa; Kevin Murray; James Gaw; Andrea Yates; Frank M. Sanfilippo; Stephen J. Nicholls (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2023)
Background: Survival during the early period following myocardial infarction (MI) has significantly improved although there are limited data on cardiovascular recurrence during this period. Methods: We identified all emergency hospitalisations for MI from November 1, 2011 to October 31, 2016 in Western Australia from a linked hospitalisation/mortality dataset. Patients were included if they survived >3 days, had no acute kidney injury, and had ≥1 of: ≥65 years, prior MI, diabetes or peripheral arterial disease. Outcomes were major adverse cardiovascular events (MACE, a composite of CVD death, recurrent MI or stroke), cardiovascular disease (CVD) death, all-cause mortality, recurrent MI and stroke. Cumulative risks at 90-days and 1-year were estimated from Kaplan-Meier analyses and predictors of each outcome from multivariable Cox regression models. Results: There were 8024 high-risk MI patients identified (males 61.8%). Median age was 73.7 years (IQR 66.3–82.2). Half of the risk of MACE occurred in the first 90-days post-MI (6.6% vs 12.6% at 1-year) and was underpinned by risk of recurrent MI. Risk was generally higher in women than men (MACE: 6.0% males, 7.7% females, p = 0.0025; CVD mortality: 1.7% males, 3.7% females; all-cause mortality: 2.8% males, 5.6% females, p < 0.0001). Independent predictors of 90-day MACE were increasing age, heart failure history, hypertension and prior stroke. Female sex was not associated with a higher rate of any of the outcomes after multivariable adjustment. Conclusion: Half of cardiovascular events in the year following an MI occur within 90-days, demonstrating that reductions in MI burden could be achieved by further targeted intervention in the early period following an MI.